Pengaruh Aktivitas Masyarakat di Sekitar Pemukiman Lahan Basah terhadap Pencemaran Air - Fariha, Aisyatu Najiyatil; i Sunarsih, Elv; Amelia, Meisya; Aditya, Muhammad Pandu; Auliya, Nur Zahrotul; Fransisca, Yolanda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Wetlands are areas of swamp, brackish, peatland and waters, permanent or temporary, with stagnant or flowing, fresh, brackish or salt water, including areas of marine waters the depth of which at low tide does not exceed six meters. Wetlands or often calledWetland is an area where water has a permanent (settled) or receding nature(seasonal). Research articles are made using research methodsliterature on a qualitative approach to obtain descriptive data.By collecting data through literature review (literature review). Based on the results of the analysis with the existencethe increase in human population over time makes many people choose other places to live than cities, such as residential areas around wetlands. Communities living around wetlands generally carry out their daily activities inseparable from the presence of water.The characteristics of people who often carry out daily activities such as bathing, cooking, washing and using floating toilets have the potential for water pollution. This is due to the lack of knowledge and public awareness, giving rise to a bad perception of environmental cleanliness. These social activities eventually have an impact on environmental quality degradation resulting in water pollution. Keywords: community activities, wetlands, water pollution